1996
DOI: 10.1016/0014-5793(96)01059-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional analysis of human PACE4‐A and PACE4‐C isoforms: identification of a new PACE4‐CS isoform

Abstract: There are seven known subtilisin/kexin-like proprorein convertases responsible for the processing of numerous precursors at either pairs or specific single basic residues. Three members, PACEA, PC4 and PC5, exhibit alternative splicing of their RNAs resulting in the generation of multiple isoforms differing in their C-or N-terminal segments. In this study we t~xamined the biosynthesis, functional activity and cellular localization of two of these isoforms, namely the full length PACE4-A and the C-terminally tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 35 publications
0
16
0
1
Order By: Relevance
“…It is unclear why the endogenous mRNA species do not seem to give rise to an active protein product in the secretory pathway. The human cDNA expressed in RPE.40 cells encoded the PACE4A isoform, and it has been suggested that this isoform and the PACE4E isoform are the only catalytically active versions of PACE4 [23,40]. Our Northern analysis shows that the PACE4 mRNA large enough to encode either of these isoforms (the largest of the four mRNA species) is only weakly expressed in RPE.40 cells ; this low level of expression could account for our inability to detect PACE4 activity.…”
Section: Discussionmentioning
confidence: 62%
“…It is unclear why the endogenous mRNA species do not seem to give rise to an active protein product in the secretory pathway. The human cDNA expressed in RPE.40 cells encoded the PACE4A isoform, and it has been suggested that this isoform and the PACE4E isoform are the only catalytically active versions of PACE4 [23,40]. Our Northern analysis shows that the PACE4 mRNA large enough to encode either of these isoforms (the largest of the four mRNA species) is only weakly expressed in RPE.40 cells ; this low level of expression could account for our inability to detect PACE4 activity.…”
Section: Discussionmentioning
confidence: 62%
“…S4F-S4H). Among previously reported PACE4 isoforms, only isoform A (PACE4-FL) is known to be active or processed from pro-PACE4 to PACE4 (23). Enzymatic activity was thus tested using recombinant (r) PACE4-FL and rPACE4-altCT (S2; Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…When present during the preincubation as well as the pulse periods, the concentrations of tunicamycin and brefeldin A (BFA) were 5 and 2.5 g/ml, respectively. As described previously (24), cells were lysed, and the proteins therein, along with those in the culture media, were immunoprecipitated by incubation with either the rPC7 antiserum (see above) plus protein A-agarose or with lentil lectin-Sepharose (25). Following SDS-PAGE, the bands were visualized by exposure to x-ray film.…”
Section: Methodsmentioning
confidence: 99%
“…The labeled proteins were then run on an SDS-PAGE, after which the appropriate bands were eluted and analyzed on an Applied Biosystem gas-phase sequenator (model 470A) as described previously (12,25).…”
Section: Methodsmentioning
confidence: 99%